2021
DOI: 10.2147/ndt.s310271
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA-Associated Competitive Endogenous RNA Regulatory Network in an Aβ25-35-Induced AD Mouse Model Treated with Tripterygium Glycoside

Abstract: Background: Tripterygium glycoside (TG) has been suggested to have protective effects on the diseases of the central nervous system including Alzheimer's disease (AD). The mechanisms involving lncRNA-associated competing endogenous RNAs (ceRNAs) were shown to play important roles in the development of AD. However, the ceRNA mechanism of TG in treating AD is still unknown. Thus, we aimed to explore the ceRNA mechanism in the treatment of AD with TG. Methods: A total of 32 C57BL/6J mice were administered 3 µL of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…One hundred and fifty-three articles were excluded for irrelevance. The full texts of the remaining 34 articles were evaluated, and 20 more articles were also excluded because they did not validate the components of the ceRNA loop using molecular techniques ( Wang et al, 2017 ; Yu et al, 2018 ; Zhou et al, 2019 ; Ma et al, 2020 ; Xu and Jia, 2020 ; Huaying et al, 2021 ; Lu et al, 2021 ; Ou et al, 2021 ; Tang et al, 2021 ; Zhang et al, 2021 ) and did not use human specimens or cell lines ( Jiang et al, 2016 ; Cai et al, 2017 ; Wang J. et al, 2018 ; Wang X. et al, 2018 ; Ma P. et al, 2019 ; Zhao et al, 2019 ; Li L. et al, 2020 ; Li X. et al, 2020 ; Yue et al, 2020 ; Zhou et al, 2020 ). Lastly, a total of 14 eligible articles remained ( Faghihi et al, 2010 ; Ke et al, 2019 ; Wang et al, 2019 ; Zeng et al, 2019 ; Zhu et al, 2019 ; Gao et al, 2020 ; Ge et al, 2020 ; Gu et al, 2020 , 2021 ; He W. et al, 2020 ; Yan et al, 2020 ; Yue et al, 2020 ; Fan et al, 2021 ; Zhang and Wang, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…One hundred and fifty-three articles were excluded for irrelevance. The full texts of the remaining 34 articles were evaluated, and 20 more articles were also excluded because they did not validate the components of the ceRNA loop using molecular techniques ( Wang et al, 2017 ; Yu et al, 2018 ; Zhou et al, 2019 ; Ma et al, 2020 ; Xu and Jia, 2020 ; Huaying et al, 2021 ; Lu et al, 2021 ; Ou et al, 2021 ; Tang et al, 2021 ; Zhang et al, 2021 ) and did not use human specimens or cell lines ( Jiang et al, 2016 ; Cai et al, 2017 ; Wang J. et al, 2018 ; Wang X. et al, 2018 ; Ma P. et al, 2019 ; Zhao et al, 2019 ; Li L. et al, 2020 ; Li X. et al, 2020 ; Yue et al, 2020 ; Zhou et al, 2020 ). Lastly, a total of 14 eligible articles remained ( Faghihi et al, 2010 ; Ke et al, 2019 ; Wang et al, 2019 ; Zeng et al, 2019 ; Zhu et al, 2019 ; Gao et al, 2020 ; Ge et al, 2020 ; Gu et al, 2020 , 2021 ; He W. et al, 2020 ; Yan et al, 2020 ; Yue et al, 2020 ; Fan et al, 2021 ; Zhang and Wang, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…et Wils [40]. , Waternut Herb [41] and extraction from traditional Chinese medicine including flavonol glycoside [42], Artemisinin [43], and TG [44–46] have been reported to exert neuroinflammation effects in AD animal models via inhibiting the expression of TNF-α. In the present study, we detected that the TNF-α mRNA was lower expressed in BM25 + AD group compared to the AD + NS group.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA networks may play roles in the pathology of AD ( Zhang et al, 2021 ), including involvement in biological metabolic processes, the cGMP-PKG signaling pathway, the Hippo signaling pathway, and axon guidance. An increasing number of ceRNA networks have been found to be associated with the pathogenesis of AD ( Huaying et al, 2020 ; Tang et al, 2021 ; Zhang et al, 2021 ). However, to the best of our knowledge, the ceRNA networks in astrocytes affected by Aβ and senescence have not been revealed.…”
Section: Discussionmentioning
confidence: 99%